A comparative study on the performance of men and women medical representatives in Iloilo City - Basa, Mark Anthony G.; Fullon, Marnelli Eileen J.; Lebiga, Jonabeth P.; Loja, Jemma L.; Lutero, Ma. Liza Conchita H.
Executive Summary - Chapter 1 of the study gives the readers a comprehensive information about the study's statement of the problem, objectives, theoretical and conceptual framework, hypotheses, assumptions, definitions of terms, scope and limitations and significance. The Statement of the problem is an assertion initiating the study. This will be answered at the end of the study after undertaking a thorough evaluation of data gathered. Moreover, the Objectives if the Study are divided into general and specific so as to clarify the goals of the study. These objectives will be accomplished by applying appropriate steps. The Theoretical and conceptual Framework serves as the skeleton of the study by classifying variables into independent intervening and dependent. The Hypotheses of the study, on the other hand, are statements that need to be proved or disprove. The assumptions of the study are presumptions made by the group in order to create a ground for uniformity during the conduct of the study. The Definition of terms enumerates and defines the words commonly used throughout the study for better understanding of the readers. The scope and limitations of the study gives the readers an insight on the boundaries of this study. and finally, the significance of the study sights the importance of this research to the readers. Chapter 2 specifies the research methodology : the research design, sampling design, method of data collection, and methods of data analysis employed in the study. This set of methods helps the researchers in achieving the objectives of the study through a step-by-step process of gathering and analysis of data. Chapter 3 collates all information related to the subject of the study through the Review of Related Literature gathered by the group. Chapter 4. gives the results of the date gathered. Analyses of the findings are supported by tables of frequencies, chi-square and correlation test values which can be found in the appendix. Chapter 5 contains the conclusion or the overall assessment of the study and recommendation made by the group for further continuance and enhancement.